2014
DOI: 10.1111/tmi.12257
|View full text |Cite
|
Sign up to set email alerts
|

Goodstart: a cluster randomised effectiveness trial of an integrated, community‐based package for maternal and newborn care, with prevention of mother‐to‐child transmission of HIV in a South African township

Abstract: Abstractbackground Progress towards MDG4 for child survival in South Africa requires effective prevention of mother-to-child transmission (PMTCT) of HIV including increasing exclusive breastfeeding, as well as a new focus on reducing neonatal deaths. This necessitates increased focus on the pregnancy and early post-natal periods, developing and scaling up appropriate models of community-based care, especially to reach the peri-urban poor.methods We used a randomised controlled trial with 30 clusters (15 in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(146 citation statements)
references
References 21 publications
(33 reference statements)
4
142
0
Order By: Relevance
“…These visits also increased infant weight and length-for-age z-scores, although no differences were found for MTCT or HIV-free survival (Tomlinson et al 2014). Similar increases in PMTCT service utilization were observed in Malawi's Tingathe PMTCT program, a CHW-based patient case management intervention (Kim et al 2012).…”
Section: Theory Of Changesupporting
confidence: 54%
See 1 more Smart Citation
“…These visits also increased infant weight and length-for-age z-scores, although no differences were found for MTCT or HIV-free survival (Tomlinson et al 2014). Similar increases in PMTCT service utilization were observed in Malawi's Tingathe PMTCT program, a CHW-based patient case management intervention (Kim et al 2012).…”
Section: Theory Of Changesupporting
confidence: 54%
“…It is well known that CHWs can enhance the reach, coverage and quality of HIV services delivered to the general population (Mwai et al 2013). However, specific evidence for leveraging this essential cadre to link community-based MNCH services with the PMTCT service cascade is small and primarily focused on infant outcomes (Kim et al 2012;le Roux et al 2013;Tomlinson et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[5] Furthermore, SA has one of the lowest exclusive breastfeeding rates in Africa (8% in infants under 6 months of age). [19] There is evidence from lowand middle-income countries, [8] including SA, [20] of the impact of CHWs undertaking breastfeeding promotion and counselling on improving exclusive breastfeeding.…”
Section: Corresponding Author: T Doherty (Tanyadoherty@mrcacza)mentioning
confidence: 99%
“…That being said, in a recently published randomized control trial conducted in KwaZulu Natal (i.e. Goodstart Cohort (10) ), with community health workers employing motivational interviewing techniques in home visits postpartum, findings showed significant increases to EBF at 12 weeks postpartum. Future research applying our IMB model-based intervention as a packaged antenatal component to a postpartum programme (e.g.…”
Section: Implications and Future Workmentioning
confidence: 99%
“…The South Africa Department of Health reports only 8 % of all women are continuing to exclusively breast-feed at 6 months (8) . In the context of research studies conducted in South Africa, EBF rates among those in the intervention arms are reported as 10 % at 6 weeks in PROMISE-EBF (9) and 28 % at 28 weeks in the Goodstart Cohort (10) . HIV stigma, HIV disclosure between partners, cultural norms surrounding breast-feeding and previous infant feeding experiences are all reported challenges to adopting EBF (11)(12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%